Nursing care in childcare services: Acantose nigricans as a marker for metabolic risk - Caroline Evelin Nascimento Kluczynik Vieira; Larissa Soares Mariz; Carla Campos Muniz Medeiros; Bertha Cruz Enders; Alexsandro Silva Coura (Universidade de São Paulo, 2013)
OBJECTIVE: to analyze the association between the presence of Acantose nigricans and metabolic changes in overweight adolescents, so as to ascertain the relevance of the identification of this marker in the nursing consultation. METHOD: a cross-sectional study undertaken between April 2009 and April 2010 with 118 adolescents who were service users of the Center for Child Obesity in Campina Grande in the Brazilian State of Paraíba (PB). The presence of Acantose nigricans, and the subjects' anthropometric measurements, were investigated. The following exams were made: insulin, triglycerides, HDL-Cholesterol, Glucose and the homeostatic model of assessment (HOMA-IR). RESULTS: there was association between the presence of Acantose nigricans and participants with insulin resistance (p=0.008), metabolic syndrome (p=0.031), elevated triglycerides (p=0.045) and altered HDL (p=0.002). CONCLUSIONS: the suggestion is supported that the detection/identification of Acantose nigricans may be used in the nursing consultation as a tool for identifying overweight adolescents with greater risk of metabolic changes.